Orthogonal partial least squares-discriminant analysis (OPLS-DA) of serum metabolomics data. - Ji-Xin Zhao (22056386) (2025)
R2X and R2Y indicate the variance explained by the X (metabolite quantification) and Y (sample grouping) matrices, respectively. Q2 represents the predictive accuracy of the model, reflecting its ability to correctly classify sample groups based on metabolic profiles. (TIF)